한국사회의 웰다잉 개념분석 - 김가혜(Kim, Gahye); 박연환(Park, Yeon-Hwan) (근관절건강학회지, 2020)
Purpose: This paper aims to clarify the concept of well-dying in the sociocultural context of Korea. Methods: Walker and Avant's method was chosen for the concept analysis. Through a literature review of 36 papers, the attributes and definition of well-dying were derived. Results: The literature revealed that in Korean society, well-dying is defined as the process of actively preparing for death throughout life. The attributes of the concept are a reflection on death, death acceptance, searching for meaning, transcendence, advance decision-making, and sharing values with family. The motivation for thinking about death, the hope of dying with dignity, and the Korean cultural view of death precede the concept, followed by dying with dignity, personal and family happiness, and improved quality of life and death. Conclusion: This study may lead to the unification of concept use based on mutual understanding, thus enabling effective communication in research, education, and clinical settings. This can be the rationale for the development of tools and educational programs as well as establishing policies related to well-dying in Korea.